2021
DOI: 10.3892/etm.2021.10892
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture regulates inflammation, collagen deposition and macrophage function in skeletal muscle through the TGF‑β1/Smad3/p38/ERK1/2 pathway

Abstract: Skeletal muscle injury is one of the most common sports injury, which accounts for ~40% of all sports-related injuries among the elderly. In addition, cases of full recovery from treatment are rare. Although electroacupuncture (EA) is an integral aspect of traditional Chinese medicine, the effects of EA on skeletal muscle fibrosis and the possible underlying mechanism remain unclear. To investigate the effect and potential mechanism of EA on skeletal inflammation, collagen deposition and macrophage function, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The TGFβ-BMP signaling is vital in embryonic bone development and postnatal bone homeostasis [ 52 ]. The TGF-βs and BMPs act on the receptor complex and transduce signals to classical Smad-dependent signaling pathways (TGF-β/BMP ligands, receptors, and Smads), and nonclassical Smad-independent signaling pathways (p38 mitogen-activated protein kinase/p38 MAPK) regulate the differentiation of mesenchymal stem cells during bone development, formation, and homeostasis [ 53 , 54 ]. The TGFβ binds to the TGFβ receptor complex to phosphorylate Smad2/3 and regulates cell functions, while the BMPs bind to the BMP receptor complex to phosphorylate Smad1/5/8 and regulate cell functions, including cell differentiation and growth [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TGFβ-BMP signaling is vital in embryonic bone development and postnatal bone homeostasis [ 52 ]. The TGF-βs and BMPs act on the receptor complex and transduce signals to classical Smad-dependent signaling pathways (TGF-β/BMP ligands, receptors, and Smads), and nonclassical Smad-independent signaling pathways (p38 mitogen-activated protein kinase/p38 MAPK) regulate the differentiation of mesenchymal stem cells during bone development, formation, and homeostasis [ 53 , 54 ]. The TGFβ binds to the TGFβ receptor complex to phosphorylate Smad2/3 and regulates cell functions, while the BMPs bind to the BMP receptor complex to phosphorylate Smad1/5/8 and regulate cell functions, including cell differentiation and growth [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMP2 has been found to be widespread in skeletal muscle, and therefore, the study of its function is important for exploring the repair of skeletal muscle after injury [ 51 ]. For example, both exogenous hydrogen sulphide and electroacupuncture treatments can improve skeletal muscle injury and reduce skeletal muscle fibrosis by downregulating MMP2 and related pathways [ 5 , 52 ]. In the present study, luteolin was found to target MMP2, which may contribute to skeletal muscle injury repair.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle injuries are one of the most common sports injuries, accounting for approximately 40% of sports-related injuries in older people [ 5 ]. Muscles can be damaged by external forces, biological factors, and chemical factors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Days post-injury, macrophage polarization and the subsequent in situ specification convert the inflammatory response to immunosuppressive starting with a series of metabolic, epigenetic and transcriptional changes characteristic of the resolution phase. During repairing, macrophages secrete cytokines such as IL-10 [ 81 , 82 ] or TFG-β [ 83 ], growth factors such as IGF-1 [ 14 ], GDF3 [ 15 , 84 ] and GDF15 [ 16 ] and lipids mediators such as Resolvin D2 [ 85 ] changing the niche and promoting regeneration.…”
Section: Regenerative Inflammation Is Regulated By Highly Coordinated...mentioning
confidence: 99%